고용형태에 따른 직무정체성, 공직봉사동기 및 조직충성도에 대한 연구 : 공항 특수경비원들의 인식을 중심으로 - 박성식; 조성환; 김광옥; 정주용; Park, Sung-Sik; Cho, Sung-Hwan; Kim, Kwang-Ok; Jung, Ju-Yong (한국항공운항학회지, 2017)
Airport security staff are outsourced workers, whose status is a special security agent under the security service law in Republic of Korea, who are subject to persuing both profitability and public concern at the same time. This paper has chosen the sample of security staff working at Incheon airport. This is because airport security staff is being outsourced, this paper had made an empirical research such areas as the perception of job identity, public service motivation and organizational commitment through job satisfaction. According to statistical research, it was found the perception on job identity by airport security staff had a significant negative effect on both job satisfaction and organizational commitment. The more they have perceived their status as non-permanent status, the less they had job satisfaction and commitment at the same time as a special security agent at airport. Their perception of job identity had a significant effect on such public service motivation factors as 'absorbing public concern' and 'a solicitude'. Lastly, their motivation factors had also significant positive effect on job satisfaction and organizational commitment.